Gaston - DiPucchio, Kelly; Robinson, Christian (New York : Atheneum Books for Young Readers, 2014)
A proper bulldog raised in a poodle family and a tough poodle raised in a bulldog family meet one day in the park.
Ages 4-8.
Accelerated Reader AR